Phytochemical investigation on the seed of Sphenostylis stenocarpa (Hochst ex A. Rich.) Harms (Family Fabaceae) - BL Nyananyo; AL Nyingifa (Journal of Applied Sciences and Environmental Management)
Phytochemical investigations carried out on the seeds of Sphenostylis stenocarpa (Hochst ex A. Rich.) Harms (Family Fabaceae) revealed the presence of the flavonoids (tricin, apigenin, chrysoeriol and genisten), tannin and alkaloids. The three putative varieties previously separated on the basis of seed colour were only distinguished on the amount of tannin present: white = 0.35, brown = 0.55 and red = 0.65. This result if corroborated by other systematic lines of evidence may lead to the delimitation of the three putative varieties into either distinct varieties or species but if otherwise could lead to the recognition of this species as monolithic. @JASEM